Mathematics of Biology - Iannelli, Mimmo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
K.L. Cooke: Delay differential equations.- J.M. Cushing: Volterra integrodifferential equations in population dynamics.- K.P. Hadeler: Diffusion equations in biology.- S. Hastings: Some mathematical problems arising in neurobiology.- F.C. Hoppensteadt: Perturbation methods in biology.- S.O. Londen: Integral equations of Volterra type.
K.L. Cooke: Delay differential equations -- J.M. Cushing: Volterra integrodifferential equations in population dynamics -- K.P. Hadeler: Diffusion equations in biology -- S. Hastings: Some mathematical problems arising in neurobiology -- F.C. Hoppensteadt: Perturbation methods in biology -- S.O. Londen: Integral equations of Volterra type.
Keywords: Mathematics; Mathematics; Mathematical and Computational Biology